MO023FLANK PAIN HAS A MAJOR NEGATIVE IMPACT ON HEALTH-RELATED QUALITY OF LIFE IN ADPKD: THE CYSTIC I STUDY. (29th May 2021) - Winterbottom, Jean; Simms, Roslyn; Caroli, Anna; Cornec-Le Gall, Emilie; Demoulin, Nathalie; Furlano, Monica; Meijer, Esther; Devuyst, Olivier; Gansevoort, Ronald; LeMeur, Yannick; Perico, Norberto; Torra, Roser; et al.
Abstract: Background and Aims: ADPKD is the most common inherited kidney disease in man, a major cause of end-stage renal disease and is a significant medical and economic burden worldwide. However, the impact of this major disease on the quality of life of patients with preserved kidney function has not been systematically explored. Method: The CYSTic I study was an observational, prospective study designed to study the natural history of ADPKD in adult patients with preserved kidney function (eGFR ≥30 ml/min/1.73m2). 465 patients were recruited from six expert centres across Europe (Belgium, France, Italy, Netherlands, Spain and UK) with baseline data recorded including HR-QoL (Health-Related Quality of Life) incorporating a Kidney Disease QOL short form questionnaire (KDQoL-SF v1.3), MRI for Total Kidney Volume (TKV) and DNA for genotyping. The cohort was stratified by baseline eGFR, Ht-TKV or genotype and correlated with HR-QOL scores. Bivariate and multivariate analyses were applied to examine the relationship between HRQoL and variables of interest. KDQoL-SF scores were calculated using an online tool provided by the Rand organisation. Results: Mean age of the participants was 44 years, 54.6% were female with a mean eGFR of 77ml/min/1.73m2 and Ht-TKV of 849ml/m. 72.3% had PKD1 mutations. 32.5% of participants reported flank pain that was not significantly correlated with eGFR, Ht-TKV or genotype. Of all the variables examined, flank pain showed significant negative associations with the highest number of KDQoL-SF subscale scores assessed (12/20). Conclusion: Our results indicate that flank pain is common, likely to be under-reported in routine care but has a major negative impact on patient-reported quality of life.